Estimation of genetic (co)variances of Gompertz growth function parameters in pigs. (13th September 2016) - Coyne, J.M.; Matilainen, K.; Berry, D.P.; Sevon‐Aimonen, M.– L.; Mäntysaari, E.A.; Juga, J.; Serenius, T.; McHugh, N.
Summary: The objective of this study was to estimate genetic (co)variances for the Gompertz growth function parameters, asymptotic mature weight ( A ), the ratio of mature weight to birthweight ( B ) and rate of maturation ( k ), using alternative modelling approaches. The data set consisted of 51 893 live weight records from 10 201 growing pigs. The growth of each pig was modelled using the Gompertz model employing either a two‐step fixed effect or mixed model approach or a one‐step mixed model approach using restricted maximum likelihood for the estimation of genetic (co)variance. Heritability estimates for the Gompertz growth function parameters, A (0.40), B (0.69) and k (0.45), were greatest for the one‐step approach, compared with the two‐step fixed effects approach, A (0.10), B (0.33) and k (0.13), and the two‐step mixed model approach, A (0.17), B (0.32) and k (0.18). Inferred genetic correlations (i.e. correlations of estimated breeding values) between growth function parameters within models ranged from −0.78 to 0.76, and across models ranged from 0.28 to 0.73 for parameter A, 0.75 to 0.88 for parameter B and 0.09 to 0.37 for parameter k . Correlations between predicted daily sire live weights based on the Gompertz growth curve parameters' estimated breeding values from 60 to 200 days of age between all three modelled approaches were moderately to strongly correlated (0.75 to 0.95). Results from this study provide heritability estimates for biologically interpretable parameters of pig growth through the quantification of genetic (co)variances, thereby facilitating the estimation of breeding values for inclusion in breeding objectives to aid in breeding and selection decisions.